THE SOCIAL RELATIONS OF IMPORTED USED ELECTRONICS MERCHANDISE IN LAGOS, NIGERIA (2016)
Imported Used Electronics (IUEs) are officially conceived in research oriented policy as potential and actual toxic “solid waste”, yet Nigeria remains a high consumer demand economy for them. IUEs include electronic monitors, digital devices, docking stations, cell phones, hand-held diagnostics, screening tools, television sets among others. Nigerian economy has evolved a socially constructed merchandise structure, which sustains IUEs trade. Literature, however limits IUEs discourses to pure-scientific framing of toxicology and dump in the Third World countries. This study, therefore, examined the subjective meanings that sustain the demand and merchandise of IUEs against official prohibition. Social action theory guided the study. The research design was exploratory. The qualitative research method was used. Data were generated from both primary and secondary sources. The research area was Lagos, and data were collected from Ikeja Computer Village, Westminster Used Electronics Market, Alaba International Market, Apapa Customs Office (ACO) and National Environmental Standards and Regulatory Enforcement Agency (NESREA). Participants were selected through purposive and snow-balling techniques. Non-participant observation for 15 months, In-depth Interviews (IDIs) were held with 22 IUE consumers and 22 market-actors. A total of 15 Key Informant Interviews (KIIs) were held with ACO officers (three), Association Heads of the three markets (eight) and veteran market actors (four). Six FGDs were conducted with IUEs consumers and market-actors, while five case studies were carried out on large scale consumers and market actors with at least 10 years working experience in IUEs merchandizing. Secondary data were sourced from NESREA and Basel Convention Coordinating Centre for Training and Technology Transfer for African Region, Ibadan. Data obtained were content analyzed. Demand for IUEs was hinged on peculiar social relations of consumption and merchandising which rationalized and constructed IUEs as desirable and affordable modern material objects. This relations involved processes of upgrading “solid waste” into tradable commodities infused with deluxe values and potentialities for leveling class. Artful transactions involved offer of disused electronics to market-actors in exchange for upgraded IUEs at a little token. A structure of interdependent actors sustained the IUEs merchandise. It included official gatekeepers such as Customs and NESREA, whose variable roles sustained entry of solid wastes into the market as IUEs; and administrators, merchants and interlinks-security who provided administrative, economic and coercive functions respectively. Furthermore, resuscitators upgrade otherwise wastes into merchandisable goods. Scavengers-collectors extract the irredeemable from merchants, to scrap-collectors who trade them to bulk-scrap-buyers. Bulk-buyers in turn, trade the scraps to domestic iron-smelting companies and/or illegally export them. In essence, IUEs remained tradable even in their end-of-life stages. Thus, local meanings of utility of IUEs and of employment potentialities were constructed against official policy perception of them as solid waste. Through a structured system of market interactions, actor-merchants contrived utility for Imported Used Electronics in the process of merchandise and consumption. Government should therefore accommodate local realities in order to proffer inclusive and robust IUEs policy.